2013
DOI: 10.4017/gt.2013.12.1.007.00
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for the feasibility of at-home online cognitive training with older adults

Abstract: Increased levels of cognitive activity may improve general cognitive function in older adults and potentially increase cognitive reserve, protecting against the onset of dementia associated with syndromes like Alzheimer's disease. To test the efficacy of cognitive training administered online, 18 participants (11 cognitively healthy; 7 mild cognitive impairment) were recruited from a clinical population of older adults to complete an online training intervention (CogniFit™). Before and after training, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Each session of the training program was further adjusted according to the progress of a given participant so that the perceived intensity of the training program is equalized. The training program was validated in Gigler et al (2013); Peretz et al (2011); Shatil (2013). The training program was embedded in digital television and allowed participants to interact with the training program in a familiar manner.…”
Section: Methodsmentioning
confidence: 99%
“…Each session of the training program was further adjusted according to the progress of a given participant so that the perceived intensity of the training program is equalized. The training program was validated in Gigler et al (2013); Peretz et al (2011); Shatil (2013). The training program was embedded in digital television and allowed participants to interact with the training program in a familiar manner.…”
Section: Methodsmentioning
confidence: 99%
“…We found 19 studies in which 11 digital cognitive training programs for older people with cognitive impairment and dementia were mentioned. The selected papers consisted of ten RCTs (Gaitán et al, 2012;Zaccarelli et al, 2013;Fiatarone Singh et al, 2014;Barban et al, 2015;Cavallo et al, 2016;Hyer et al, 2016;Suo et al, 2016;Bahar-Fuchs et al, 2017;Hagovská et al, 2017;Cavallo and Angilletta, 2018), five pre-post studies (Gigler et al, 2013;González-Palau et al, 2014;Hwang et al, 2015;Vermeij et al, 2017;Mendoza Laiz et al, 2018), two studies with repeated measures design (Eckroth-Bucher and Siberski, 2009;Vermeij et al, 2016), one pilot study (Danassi, 2015), and one study protocol for an RCT (Vanova et al, 2018).…”
Section: Characteristics Of Computerized Programsmentioning
confidence: 99%
“…The study showed that people with MrNPS performed overall better than participants with MCI in global cognitive ability. Another study aimed to explore the potential of CogniFit in people with MCI and healthy adults (Gigler et al, 2013). The prepost study found that participants in the cognitive training condition improved on global cognition and memory after the intervention.…”
Section: Cognitive Stimulation Programmentioning
confidence: 99%
“…Each session of the training program was further adjusted according to the progress of a given participant so that the perceived intensity of the training program is equalized. The training program was validated in (Gigler et al, 2013;Peretz et al, 2011;Shatil, 2013 Manuscript to be reviewed digital television and allowed participants to interact with the training program in a familiar manner. Television as a low-cost training device was assessed with favourable results in Boquete et al (2011).…”
Section: Interventionmentioning
confidence: 99%